1996
DOI: 10.1101/gad.10.20.2632
|View full text |Cite
|
Sign up to set email alerts
|

RAD9 and DNA polymerase epsilon form parallel sensory branches for transducing the DNA damage checkpoint signal in Saccharomyces cerevisiae.

Abstract: In response to DNA damage and replication blocks, yeast cells arrest at distinct points in the cell cycle and induce the transcription of genes whose products facilitate DNA repair. Examination of the inducibility of RNR3 in response to UV damage has revealed that the various checkpoint genes can be arranged in a pathway consistent with their requirement to arrest cells at different stages of the cell cycle. While RADg, RAD24, and MEC3 are required to activate the DNA damage checkpoint when cells are in G1 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
130
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(135 citation statements)
references
References 49 publications
(62 reference statements)
5
130
0
Order By: Relevance
“…The same study found that the mutator phenotype of the pol2-4 allele was unaffected by the absence of Dun1. This result is surprising, given the role of Pol e in helping to mediate the S-phase checkpoint (40)(41)(42)(43)(44). However, the weak pol2-4 mutator phenotype or the acquisition of a suppressor mutation may have limited the ability to detect a decrease in mutation rate in dun1Δ strains.…”
mentioning
confidence: 47%
“…The same study found that the mutator phenotype of the pol2-4 allele was unaffected by the absence of Dun1. This result is surprising, given the role of Pol e in helping to mediate the S-phase checkpoint (40)(41)(42)(43)(44). However, the weak pol2-4 mutator phenotype or the acquisition of a suppressor mutation may have limited the ability to detect a decrease in mutation rate in dun1Δ strains.…”
mentioning
confidence: 47%
“…7C). This could be explained by the fact that both Chk1 and Rad53 contribute to the DNA damage checkpoint downstream of Rad9, and Rad53 also requires Rad9 for signal amplification (20,21). Additionally, activated Chk1 may not be able to compensate for the loss of other Rad9 functions such as blocking processing of telomeres in cdc13-1 cells (22).…”
Section: Mec1mentioning
confidence: 95%
“…Indeed, a link between pol and checkpoint activation, including the physical interaction between DinB and Hus1 and Rad1, was recently reported in Schizosaccharomyces pombe (49). Similarly, pol⑀ was reported to be a checkpoint protein (50). The experiments presented in this study provide evidence for the direct involvement of pol in TLS across BP-G adducts in living cells, since cells lacking pol exhibited a 3-fold reduction in TLS across this lesion, and expression of human pol in these cells resulted in complementation of the bypass defect.…”
Section: Bypass Of Bp-g Adducts By Pol In Mammalian Cellsmentioning
confidence: 99%